PENGAJARAN BAHASA ARAB DENGAN CONTEXTUAL LEARNING PONDOK PESANTREN AL IKHLAS DI DAWAR, MANGGIS, MOJOSONGO, BOYOLALI, JAWA TENGAH - rohmat, Rohmat (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
The research aims at two main things. The first, to find out the characteristics of contextual learning in teaching Arabic language at Pondok Pesantren Al Ikhlas in Dawar, Manggis, Mojosongo, Boyolali, Jawa Tengah. Second, to find out the components of contextual learning applied in teaching Arabic language at Pondok Pesantren Al Ikhlas. The research applies descriptive non hipothetical approach. The population is 220 santri, and the sample is 50 santri in random. The instrument for collecting  data is validity questionair with try out. Data analysis uses percent analysis. The result of research: 1) the characteristic of contextual learning involve collaboration, support each other; it is fun, not boring; learn in passion; integrated learning; use many resources, active students; sharing with friends; students are critical and creative teachers are just suited in teaching Arabic language at Pondok Pesantren Al Ikhlas in Dawar, Manggis, Mojosongo, Boyolali, Jawa Tengah. 2)  components of contextual learning  involve: related meaning; independent learning and collaboration, critical and creative thinking, helping students to grow and develop, reaching high standard and authentic thinking and the contextual learning strategy  is not found out unsuited in teaching Arabic language  at  Pondok Pesantren Al Ikhlas in Dawar, Manggis, Mojosongo, Boyolali, Jawa Tengah.Keywords: Pengajaran Bahasa Arab, Pengajaran Kontekstual